A FLAVONOL COMPOUND FROM Chingia sakayensis (Zeiller) Holtt AND ITS ACTIVITY AS DPPH FREE RADICAL SCAVENGER - Suyatno Suyatno; Rukmaningsih Rukmaningsih; Noor Cholies Zaini; Motoo Tori (Indonesian Journal of Chemistry, 2003)
It has been separated a flavonol 3,5,7,4'-tetrahydroxy flavone (kaemferol) from the methanol extract partitioned by ethyl acetate of the leaves of the fern Chingia sakayensis (Zeiller) Holtt. This was obtained as yellow crystals with m.p. 271-273oC. Characterization of its molecular structure was carried out by spectroscopic methods (UV, IR, 1H-NMR, HMQC, HMBC, 13C-NMR and FABMS). Kaemferol indicated the DPPH free radical scavenger activity in TLC autography.